Contingência e necessidade na causalidade externa segundo Ockham: Argumentos para revisar a interpretação dominante - Fernández, Carolina Julieta (2010)
In this paper we provide a summary of what, we believe, has been the dominant trend in the interpretation of Ockham´s doctrine of causality from the past three or four decades up to the present. We intend to develop three strategies to criticise this interpretation, each one belonging to a different level: ontology and language in the first place, physics in the second one and epistemology in the third one. The result of our exploration is a less optimistic view of Ockham's doctrine of causality than the dominant.